2020
DOI: 10.2147/jpr.s255249
|View full text |Cite
|
Sign up to set email alerts
|

<p>CT-Guided Percutaneous Lumbar Ligamentum Flavum Release by Needle Knife for Treatment of Lumbar Spinal Stenosis: A Case Report and Literature Review</p>

Abstract: Point your mobile at the code above. If you have a QR codereader, the video abstract will appear. Or use: https://youtu.be/xUgzwLiZT5c Case: The patient was a 62-year-old woman presenting with low-back pain of 3 years' duration and numbness in the right leg. Diagnosis: She was diagnosed with lumbar spinal stenosis based on combined magnetic resonance imaging, physical examination, and symptoms. Interventions: Treatment with computed tomography-guided percutaneous release of the ligamentum flavum was delivered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Middle-and old-age patients with LSS may have thickened ligamentum flavum of the lumbar spine. A study on the effective acupotomy depth for LSS 24 showed that the sufficient depth to treat the ligamentum flavum should be approached to an average depth of ≥5 cm. The length of the acupotomy used in this study was 5 cm, indicating that the depth of stimulation around the spine was shallow.…”
Section: Discussionmentioning
confidence: 99%
“…Middle-and old-age patients with LSS may have thickened ligamentum flavum of the lumbar spine. A study on the effective acupotomy depth for LSS 24 showed that the sufficient depth to treat the ligamentum flavum should be approached to an average depth of ≥5 cm. The length of the acupotomy used in this study was 5 cm, indicating that the depth of stimulation around the spine was shallow.…”
Section: Discussionmentioning
confidence: 99%
“…[29] TGF-β1 has been reported to be one of the most prominent molecules causing collagen deposition, [30] while angiopoietin-like protein 2 is closely associated with chronic inflammation in LF fibroblasts. [31] Zhu et al [32] treated an elderly patient with LSS due to LFH by needle knife under CT-guidance. The symptoms were relieved immediately after treatment, completely disappeared after 1 month, and did not recur during the one-year follow-up.…”
Section: Nonsurgical Treatment Of Lssmentioning
confidence: 99%
“…10,11 Studies have shown that ligamentum flavum hypertrophy (LFH), mostly resulting from facet degenerative changes, or its anterior buckling into the spinal canal as leading causes of spinal canal stenosis and disc space narrowing. [12][13][14] On the other hand, spine instability and instrumented laminectomies are also linked to LFH and canal narrowing at the segments adjacent to the intervention. [15][16][17][18][19] Mechanistically, LFH is implicated in degenerative lumbar spinal stenosis resulting from direct compression of the spinal canal involving the cauda equina, reduction in the anteroposterior diameter (APD) of the intervertebral foramen, squeezing of the nerve roots with numbness and LBP symptoms, and painful lower extremities.…”
Section: Introductionmentioning
confidence: 99%